Analisis Efektivitas Biaya Terapi Antihipertensi pada Pasien Rawat Inap Covid-19 dengan Hipertensi di RSUD Panembahan Senopati Bantul Yogyakarta - Fitri Andriani Fatimah; Anis Febri Nilansari; Rahmat A Hi Wahid (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2022)
Abstract. Hypertension is the highest comorbid group of Covid-19patients, which is 50.5%, followed by diabetes mellitus 34.5% and heart disease 19.6%. Most hypertensive patients have blood pressure that is not controlled with single therapy, while the cost of treatment is increasing every year. The presence of comorbid hypertension in Covid19 patients has an impact on increasing costs, with the highest average cost being in pharmaceutical costs. This needs to be analyzed to find out which antihypertensive drugs are the most cost-effective and provide the best therapeutic outcomes, especially during the Covid-19pandemic. The purpose of this study was to determine the most costeffective antihypertensive therapy in hypertensive patients with Covid19 in 2020-2022 at Panembahan Senopati Hospital, Bantul, Yogyakarta. This study uses a non-experimental research method that is descriptive analytic. Data was collected retrospectively based on medical records, laboratory results and drug price ceilings in the hospital administration. Cost-effectiveness analysis was carried out by comparing the average direct medical cost to the percentage of patients whose blood pressure reached the target based on ACER parameters and was declared cured (the results of the swab-test or PCR examination were declared negative). The results of the study on 63 Covid-19 patients with hypertension showed that the most costeffective antihypertensive drug class for hypertension monotherapy was the CCB group, the most cost-effective combination of 2 antihypertensive therapies was the ARB and Diuretics and the 3 most costeffective combination of antihypertensive drug classes. effective is a combination of BB, ACEI and diuretics.